PENGARUH FINANCIAL KNOWLEDGE, PEER INFLUENCE, DAN FINANCIAL ATTITUDE TERHADAP SAVING BEHAVIOR GENERASI Z DI KECAMATAN CILEUNGSI - Arini, Widya Septy (Robust: Research of Business and Economics Studies, 2024)
Saving behavior is a stage in decision making to save some income or money that is routinely owned in achieving an individual's financial goals. This study aims to examine the influence between financial knowledge, peer influence, financial attitude, and saving behavior of generation Z in Cileungsi District. The sampling technique used purposive sampling method with data collected as many as 207 respondents who live in Cileungsi District. This research uses primary data obtained through distributing questionnaires using google forms which are then distributed online on various social media or directly. The analysis method uses descriptive analysis and Structural Equation Model (SEM) PLS. The results indicate that financial knowledge has a positive effect on saving behavior, peer influence has no significant effect on saving behavior and financial attitude has a positive effect on saving behavior of generation Z in Cileungsi District.